The Psychophysiology of Action: A Multidisciplinary Endeavor for Integrating Action and Cognition - Hoffmann, Sven; Borges, Uirassu; Bröker, Laura; Laborde, Sylvain; Liepelt, Roman; Lobinger, Babett H.; Löffler, Jonna; Musculus, Lisa; Raab, Markus (Frontiers in Psychology, 2018)
There is a vast amount of literature concerning the integration of action and cognition. Although this broad research area is of great interest for many disciplines like sports, psychology and cognitive neuroscience, only a few attempts tried to bring together different perspectives so far. Our goal is to provide a perspective to spark a debate across theoretical borders and integration of different disciplines via psychophysiology. In order to boost advances in this research field it is not only necessary to become aware of the different areas that are relevant but also to consider methodological aspects and challenges. We briefly describe the most relevant theoretical accounts to the question of how internal and external information processes or factors interact and, based on this, argue that research programs should consider the three dimensions (a) dynamics of movements; (b) multivariate measures and; (c) dynamic statistical parameters. Only with an extended perspective on theoretical and methodological accounts, one would be able to integrate the dynamics of actions into theoretical advances.